EICOSANOIDS AND INFLAMMATION - A. E. Karateev; T. L. Aleinikova (Современная ревматология)
Inflammation is the most important element in the pathogenesis of major human diseases. It determines the fundamental value of anti-inflammatory therapy in the modern concept of targeted pathogenetic treatment. The rational choice of anti-inflammatory drugs and the design of new promising agents are inconceivable without clear knowledge of the characteristics of development of an inflammatory response. Eicosanoids, the metabolites of polyunsaturated fatty acids, play a key role in the process of inflammation. These substances have diverse and frequently antagonistic biological effects, which is determined by their chemical structure and specific features of receptors with which they interact. Some of them (prostaglandins, leukotrienes, auxins, and hepoxilins) are potential mediators of inflammation and pain; others (lipoxins, epoxyeicosatrienoic acid derivatives, resolvins, protectins, maresins, and endocannabinoids) have anti-inflammatory and cytoprotective activities, contributing to the resolution of the inflammatory response. This review describes considers the main classes of eicosanoids, their metabolism, effects, and clinical significance, as well as the possibilities of pharmacological interventions in their synthesis or interaction with receptors.